Measurement of the Inclusive Electron Neutrino Charged Current Cross Section on Carbon with the T2K Near Detector. - Abe, K; Adam, J; Aihara, H; Akiri, T; Andreopoulos, C; Aoki, S; Ariga, A; Assylbekov, S; Autiero, D; Barbi, M; Barker, G; Barr, G; et al. (American Physical Society, 2014)
The T2K off-axis near detector ND280 is used to make the first differential cross-section measurements of electron neutrino charged current interactions at energies ∼1  GeV as a function of electron momentum, electron scattering angle, and four-momentum transfer of the interaction. The total flux-averaged ν_{e} charged current cross section on carbon is measured to be ⟨σ⟩_{ϕ}=1.11±0.10(stat)±0.18(syst)×10^{-38}  cm^{2}/nucleon. The differential and total cross-section measurements agree with the predictions of two leading neutrino interaction generators, NEUT and GENIE. The NEUT prediction is 1.23×10^{-38}  cm^{2}/nucleon and the GENIE prediction is 1.08×10^{-38}  cm^{2}/nucleon. The total ν_{e} charged current cross-section result is also in agreement with data from the Gargamelle experiment.